Adverse events of hepatic anti-fibrotic agents in phase 3 and above clinical trials: a descriptive analysis of the WHO-VigiAccess database - Liu, Yuwei; Zhao, Xu; Wang, Xinrui; Zhou, Qiang (Frontiers in Pharmacology, 2025)
IntroductionLiver fibrosis is a pathological condition in response to chronic liver injuries. Currently, there is no Food and Drug Administration (FDA) approved pharmacotherapy for liver fibrosis. Advances in understanding hepatic fibrogenesis have led to the development of anti-fibrotic agents, and some of them have shown promise in phase 3 and above clinical trials. However, adverse drug reactions (ADRs) associated with emerging anti-fibrotic agents may hinder their efficacy and clinical applicability. This study assessed ADRs associated with anti-fibrotic agents as reported in the World Health Organization (WHO) VigiAccess database and compared the adverse reaction characteristics of these agents for optimizing therapeutic strategies.MethodsA detailed search was conducted on ClinicalTrial.gov to identify phase 3 or 4 clinical trials involving hepatic anti-fibrotic agents. The ADR reports were retrieved from the WHO-VigiAccess database, with data categorized by demographic characteristics, geographic distribution, and System Organ Classes (SOCs). The most frequently reported ADRs were identified through descriptive analysis. Disproportionality analysis, measured by reporting odd ratio (ROR) and proportional reporting ratio (PRR), was performed to evaluate ADRs related to gastrointestinal disorders.ResultsFive hepatic anti-fibrotic agents (empagliflozin, liraglutide, candesartan, obeticholic acid, and resmetirom) were identified. A total of 130,567 ADR reports were analyzed, with empagliflozin, liraglutide, and candesartan showing significantly higher ADRs. The most frequently reported SOCs included gastrointestinal disorders (29.44%), general disorders (24.12%), and nervous system disorders (14.42%). Liraglutide demonstrated a higher risk of gastrointestinal ADRs (ROR: 4.629, 95% CI: 4.517–4.744; PRR: 3.566, 95% CI: 3.492–3.642) compared to the other agents. Severe ADRs were reported in empagliflozin, such as ketoacidosis and infections, while liraglutide was associated with pancreatitis and candesartan with acute kidney injury. Serious ADR rates varied, with candesartan reporting the highest proportion (7.28%).ConclusionWhile hepatic anti-fibrotic agents showed promise in addressing liver fibrosis, their ADR profiles underscore the importance of pharmacovigilance and personalized treatment approaches. Future efforts should focus on improving the pharmacovigilance system, expanding population diversity in trials, and conducting ongoing research and extensive post-marketing surveillance.